Implementation of Inquiry Methods to Improve Qur'an Hadits Learning Outcomes of Students of CLASS IIIB MI Maulana Maghribi Bantul - Uswatun Hasanah (Universitas Tadulako, 2021)
This research aimed to improve student learning outcomes using the inquiry method in the Qur'an Hadith material. This research was a classroom action research conducted in 2 cycles. Each cycle's steps adopted the steps suggested by Kemmis and Taggart; planning, acting, observing, and reflecting. The research subjects were 21 students (14 girls and 7 boys) in class IIIB MI Maulana Maghribi Bantul. Data were collected through test and non-test (observation) techniques. Data were analyzed using the quantitative descriptive method. The research is said to be successful if students who reach the KKM are at least 75%. The results obtained were that the average learning outcomes in cycle 2 increased by 20.5%, from 74.3 to 89.5. The number of students who reached the KKM in cycle 2 was 90.5%. Student participation in cycle 2 reached 80%.